The Problems of The Marriage Age Changing in Indonesia in the Perspectives of Muslim Jurists and Gender Equality - Zulaiha, Eni; Mutaqin, Ayi Zaenal (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2021)
The rules regarding the age limit for marriage as contained in Article 7 of Law no. 1 of 1974, which states that the minimum age of marriage for men is 19 years and for women is 16 years. These rules were amended through law no. 16 of 2019, which stipulates that the age limit for marriage, both for men and women, are in the same age, 19 years old. This change is intended to bring benefits of marriage minimizes the conflict in the household. But in fact, the changing age limit for marriage still creates some problems; for example, not a few Muslims view that in Islam, there are no provisions regarding age limits and there are dispensations for those forced to marry under a predetermined age. This research aims to find out the problematics of the law on changing the age limit for marriage. The research approach used qualitative with descriptive analysis methods and literature review. The results of the study indicate that there are several problems regarding the age limit between First, Islamic law does not stipulate a minimum age for marriage, so that some people do not heed the provision; Second, there are some rules regarding dispensation for those who want to get married at the age of 19 by putting forward to the court. This is an opportunity to violate the regulations; Third, changes to the law that have raised the age limit for marriage, in reality, in society, have not been able to stop the rate of early-age marriage.